Association of non-HLA antibodies against endothelial targets and donor-specific HLA antibodies with antibody-mediated rejection and graft function in pediatric kidney transplant recipients - Fichtner, Alexander; Süsal, Caner; Höcker, Britta; Rieger, Susanne; Waldherr, Rüdiger; Westhoff, Jens; Sander, Anja; Dragun, Duska; Tönshoff, Burkhard (Pediatric nephrology, 2021)
Background Non-HLA antibodies against endothelial targets have been implicated in the pathogenesis of antibody-mediated rejection (ABMR), but data in pediatric patients are scarce. - Methods We retrospectively analyzed a carefully phenotyped single-center (University Children’s Hospital Heidelberg, Germany) cohort of 62 pediatric kidney transplant recipients (mean age at transplantation, 8.6 ± 5.0 years) at increased risk of graft function deterioration. Patients had received their transplant between January 1, 1999, and January 31, 2010. We examined at time of late index biopsies (more than 1-year post-transplant, occurring after January 2004) the association of antibodies against the angiotensin II type 1 receptor (AT1R), the endothelin type A receptor (ETAR), the MHC class I chain-like gene A (MICA), and vimentin in conjunction with overall and complement-binding donor-specific HLA antibodies (HLA-DSA) with graft histology and function. - Results We observed a high prevalence (62.9%) of non-HLA antibody positivity. Seventy-two percent of HLA-DSA positive patients showed additional positivity for at least one non-HLA antibody. Antibodies against AT1R, ETAR, and MICA were associated with the histological phenotype of ABMR. The cumulative load of HLA-DSA and non-HLA antibodies in circulation was related to the degree of microinflammation in peritubular capillaries. Non-HLA antibody positivity was an independent noninvasive risk factor for graft function deterioration (adjusted hazard ratio 6.38, 95% CI, 2.11-19.3). - Conclusions Our data indicate that the combined detection of antibodies to HLA and non-HLA targets may allow a more comprehensive assessment of the patients’ immune responses against the kidney allograft and facilitates immunological risk stratification.
Korrigierte Veröffentlichung 2021
Gesehen am 24.04.2023